1968
DOI: 10.1063/1.1656412
|View full text |Cite
|
Sign up to set email alerts
|

New Vitreous Semiconductors

Abstract: Coevaporation with vapor quenching has been used to combine metallic and nonmetallic elem.ents into new vitreous semiconductors. These binary glasses, formed with an excess of nonmetal over. a wide ran.ge of compositions exhibit semiconducting and optical properties differing from the correspondmg proper~Ies of either component alone or of any known crystalline compound formed between the comp.onents. Detal~e? investigation of the vitreous Bi-Se system indicates that an inten;ne?iate temperature :el?~n of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…It has been known that Bi can change the electronic configurations in chalcogenide types of glasses, which results in the changes in their electrical properties. 30,31 Bi enters the network in the form of a charged species and alters the ratio of Valence Alternation Pairs (VAPs) to such an extent that the Fermi level of the GeBiTe becomes unpinned. 32 It is also reported that Bi changes the coordination from threefold and fourfold showing a positive charge to twofold and sixfold showing a negative charge.…”
Section: Resultsmentioning
confidence: 99%
“…It has been known that Bi can change the electronic configurations in chalcogenide types of glasses, which results in the changes in their electrical properties. 30,31 Bi enters the network in the form of a charged species and alters the ratio of Valence Alternation Pairs (VAPs) to such an extent that the Fermi level of the GeBiTe becomes unpinned. 32 It is also reported that Bi changes the coordination from threefold and fourfold showing a positive charge to twofold and sixfold showing a negative charge.…”
Section: Resultsmentioning
confidence: 99%
“…The goal was the preparation of new infrared photodetectors. At the same time, it was discovered that a small amount of Bi atoms incorporated in a selenium matrix changes the electrical conductivity from p to n type [3]. More recently, the possibility of making an all chalcogenide glass p-n junction based on the ability of Bi to change the conductivity type was demonstrated [4,5].…”
Section: Introductionmentioning
confidence: 98%